Wall Temperature Effects on the Reynold Stress of Flat-Plate Turbulent Boundary Layer: A Numerical Investigation (Advances in Applied Mathematics and Mechanics, 2019)
In this paper, direct numerical simulation (DNS) of spatially evolving flat-plate hypersonic turbulent boundary layer with free-stream Mach number 8 is used to study the effects of wall temperature on compressibility and Reynolds stress contribution. The DNS contains two cases with different wall temperatures, $T_w$/$T_∞$=$10.03$ and $1.9$. The results show that lower wall temperature enhances both the compressibility and injection-and-sweeping motions near the wall.